Teaching writing skills in online paleontology and evolution courses - Dewar, Eric W.; Gold, M. Eugenia L.; Dwyer, Heather (Frontiers in Education, 2022)
Though foundational knowledge and technical skills are frequently and rightfully emphasized in biology curricula, transferrable skills, including writing, are under-prioritized to the detriment of biology graduates and to the scientific field. In an effort to target this gap, we designed assessments in online paleontology and evolution courses to foster critical analysis, synthesis, and written communication skills among students. This article describes model writing assignments for a variety of college courses at different levels and for different audiences. For example, appropriate analysis and comparison of major texts like Darwin’s On the Origin of Species by Means of Natural Selection can be approached by students in general education courses as well as upper-level science students within their major. In another assignment, upper-level science students write to assess the effectiveness of novel characters in phylogenetic systematics. Last, we describe an assignment that introduces students to paleoecological interpretation to develop expository writing skills for scientists and non-scientists alike.